Analysis of common shoulder injuries in collegiate baseball players - Vargas, L.; Charen, D.; Huang, H.; Poeran, J.; Colvin, A. (The Physician and Sportsmedicine, 2022)
Objectives Baseball players are highly susceptible to shoulder injuries due to repetitive overhead throwing. The purpose of this study was to investigate men`s collegiate baseball shoulder injury rates and associated risk factors.